The Relationship Between Formula Milk Feeding and the Incidence of Acute Diarrhea in Babies 0-6 Months - Ginting, Brigita Sari Kristina Br.; Pantow, Sefry M.; Siregar, Muchtar Nora Ismail; Jusuf, Muhammad Isman; Ibrahim, Sri Andriani (Formosa Journal of Sustainable Research, 2025)
Diarrhea is a common disease in newborns and toddlers that can cause death. One of the factors that causes diarrhea in babies is a lack of exclusive breastfeeding or failure to breastfeed for two years. Exclusive breastfeeding for 4 to 6 months is often considered a preventative measure against allergies and some diseases, including infections and diarrhea. The author intends to examine the relationship between formula milk consumption and the incidence of diarrhea in infants aged 0-6 months at Prof. Hospital. Dr. H. Aloei Saboe Gorontalo City. This study used an analytical observational design with a cross-sectional approach. The research sample consisted of 32 newborn babies who met the inclusion and exclusion criteria at RSUD Prof. Dr. H. Aloei Saboe Gorontalo City. Data analysis was carried out univariate and bivariate using the Pearson Chi-Square test. The results for choosing the type of cow's milk formula were 83.8%, the results for the method of giving formula milk were found to be 75.7% which did not comply with the provisions, and the results for the method of making formula milk were found to be 72.0% which were not in accordance with the provisions. There is a relationship between the method of administration, selection and manufacture of formula milk and the incidence of acute diarrhea in infants with p<0.05. There is a significant relationship between giving formula milk and the incidence of diarrhea in babies 0-6 months at Aloe Saboe Hospital, Gorontalo. It is hoped that the public will be aware of how important cleanliness is in serving formula milk to babies